The death dealer - Graham, Heather (Mira, 2008)
As a killer obsessed by Poe's macabre tales selects his victims from members of a literary society devoted to the master writer, author Genevieve O'Brien, fearing that her mother will be next, enlists the aid of P.I. Joe Connolly to stop the murders.